The Role Of The Cadre For Family Development (BKB) In Improving The Competency Of Childhood Mother In Demak - Suemy .; Sri Katoningsih (Universitas Muhammadiyah Ponorogo, 2021)
The role of parents is crucial in the development and growth of earlychildhood thinking skills. Early childhood is able to master more words andhave a strong desire to understand everything. Cadres are human resourcesinvolved in BKB counseling activities. The purpose of this study is todescribe and analyze the role of BKB cadres in improving the competence ofmothers under five in Demak Regency. This research is a qualitativeresearch. The subjects of this study were BKB cadres in Demak Regency.Data collection techniques through observation, interviews and documentstudy. Data analysis techniques by collecting data then reducing data,analyzing and then concluding. The results of this study indicate that BKBcadres have a very crucial role, namely as facilitators and as motivators.Efforts made by BKB cadres to increase the knowledge and insight ofmothers under five by building commitment, fostering motivation, abilitiesand skills, conducting continuous coaching, conducting evaluation andmonitoring.